2014
DOI: 10.1242/jcs.157966
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Hedgehog release from pancreatic cancer cells increases paracrine signaling potency

Abstract: Members of the Hedgehog (Hh) family of morphogens play crucial roles in development but are also involved in the progression of certain types of cancer. Despite being synthesized as hydrophobic dually lipid-modified molecules, and thus being strongly membraneassociated, Hh ligands are able to spread through tissues and act on target cells several cell diameters away. Various mechanisms that mediate Hh release have been discussed in recent years; however, little is known about dispersion of this ligand from can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…S3). This observation is in line with the described shedding of endogenous Shh from the PANC1 cell surface (Damhofer et al, 2015). We confirmed Shh-HA shedding from PANC1 cells by the nonphysiological and physiological release factors MβCD and Scube2, as indicated by enhanced electrophoretic product mobility in comparison to the cell-bound protein precursor (Fig.…”
Section: The Heparan Sulfate Source Determines Shh Processingsupporting
confidence: 90%
See 2 more Smart Citations
“…S3). This observation is in line with the described shedding of endogenous Shh from the PANC1 cell surface (Damhofer et al, 2015). We confirmed Shh-HA shedding from PANC1 cells by the nonphysiological and physiological release factors MβCD and Scube2, as indicated by enhanced electrophoretic product mobility in comparison to the cell-bound protein precursor (Fig.…”
Section: The Heparan Sulfate Source Determines Shh Processingsupporting
confidence: 90%
“…2A). We and others have shown that proteolytic removal of N-and C-terminal lipidated peptides (called shedding) releases bioactive Shh morphogens from the surface of producing cells in vitro (Damhofer et al, 2015;Dierker et al, 2009;Jakobs et al, 2014;Ohlig et al, 2011). We further showed that because of the lack of the N-terminal Hhat acceptor cysteine (C25S or C25A in mouse Shh) (Hardy and Resh, 2012) non-palmitoylated Hh proteins require only C-terminal shedding for their solubilization, whereas most Shh N-termini are left intact (Jakobs et al, 2014).…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophmentioning
confidence: 89%
See 1 more Smart Citation
“…Signaling through paracrine mechanisms between homotypic and heterotypic cells results in increasing cancer survival and therapeutic resistance. 32,33 Furthermore, apoptosis-related cellular processes can initiate or deactivate responses in surrounding cells. 34,35 Droplet microfluidics provides a suitable platform for characterizing cytotoxic drug uptake and apoptosis in single cells without affecting the functionality of adjacent cells.…”
Section: Introductionmentioning
confidence: 99%
“…So, GLI1 expression leads to a positive feed-back loop, and it acts as a constitutive activator24. In most cases, GLI1 overexpression is considered as a symbol of HH pathway activation32. Other than canonical HH pathway, the non-canonical activation pathways are defined as any form of signaling relating to HH pathway components that differs from the usual HH pathway paradigm27.…”
Section: Introductionmentioning
confidence: 99%